Challenges Facing Asian International Graduate Students in the US: Pedagogical Considerations in Higher Education - Lin, Shu-Yuan; Scherz, Susan Day (Journal of International Students, 2014)
Non-Native English Speaking (NNES) international students attending colleges and universities in the United States often encounter difficulties in adjusting to their new cultural environment. In addition, they often struggle with academic language while learning the content and conceptual structures of various graduate level disciplines. This phenomenological study identified cultural and linguistic challenges experienced by NNES Asian international graduate students at a mediumsized rural university in the northwestern United States. A pedagogical framework and recommendations for professional practice address the linguistic, cultural, and academic needs of this particular student population in higher education.